UPAYA MEDIASI DALAM PENYELESAIAN SENGKETA EKONOMI SYARI’AH DI PENGADILAN AGAMA PADANG KELAS IA - Iyah Faniyah; Evi Sumarni (LPPM Universitas Ekasakti Padang, 2022)
The Religious Courts based on Article 49 of the Law on Religious Courts have expanded their authority to settle sharia economic cases. Based on Article 10 of PERMA Number 14 of 2016 concerning Procedures for Settlement of Sharia Economic Disputes, it is emphasized that judges in ordinary examination procedures must seek reconciliation through mediation. In practice, mediation efforts are often unsuccessful, as happened in the Padang Religious Court, of the 4 sharia economic cases that were entered, only one case was successfully mediated. Based on the results of the research, discussion and analysis, it can be concluded: first, mediation efforts in resolving Sharia economic disputes at the Padang Religious Court are mediators using informative, educative and persuasive methods. In the Padang Religious Court, there are internal factors: (1) mediators from judges who do not have certificates, (2) mediation seems only a formality, External factors: (1) litigants who are reluctant to be mediated, (2) The place to hold mediation is not yet conducive so it is not comfortable to negotiate